Investigating the efficacy of an individualized metacognitive therapy program (MCT+) for psychosis: study protocol of a multi-center randomized controlled trial - Schneider, Brooke C.; Zink, Mathias (BMC psychiatry, 2016)
Background: Psychological interventions are increasingly recommended as adjunctive treatments for psychosis, but their implementation in clinical practice is still insufficient. The individualized metacognitive therapy program (MCT+; www.uke.de/mct_plus) represents a low-threshold psychotherapeutic approach that synthesizes group metacognitive training (MCT) and cognitive behavioral therapy for psychosis, and addresses specific cognitive biases that are involved in the onset and maintenance of psychosis. It aims to “plant the seed of doubt” regarding rigid delusional convictions and to encourage patients to critically reflect, extend and change their approach to problem solving. Its second edition also puts more emphasis on affective symptoms. A recent meta-analysis of metacognitive interventions (MCT, MCT+) indicate small to moderate effects on positive symptoms and delusions, as well as high rates of acceptance. Nonetheless, no long-term studies of MCT+ involving large samples have been conducted. Methods: The goal of the present multi-center, observer-blind, parallel-group, randomized controlled trial is to compare the efficacy of MCT+ against an active control (cognitive remediation; MyBrainTraining©) in 328 patients with psychosis at three time points (baseline, immediately after intervention [6 weeks] and 6 months later). The primary outcome is change in psychosis symptoms over the 6-month follow-up period as assessed by the delusion subscale of the Psychotic Symptom Rating Scale. Secondary outcomes include jumping to conclusions, other positive symptoms of schizophrenia, depressive symptoms, self-esteem, quality of life, and cognitive insight. The study also seeks to elucidate mediating factors that promote versus impede symptom improvement across time. Discussion: This is the first multi-center randomized controlled trial to test the efficacy of individualized MCT+ in a large sample of patients with psychosis. The rationale for the trial, the design, and the strengths and limitations of the study are discussed.